Analysis of methods for calculating spur gear for deep contact strength - S. Yu. Lebedev (Архитектура, строительство, транспорт)
Spur gear is an integral part of transport and technological machines structure. To increase the load ability of the spur gear, chemical heat treatment of the working cogs surfaces is used. Spur gear with chemical heat treatment must be checked for deep contact strength. The article analyzes various methods (according to GOST 21354-87, methods using the generalized criterion of the limit state for structurally inhomogeneous material by Lebedev-Pisarenko, methods from the handbook describing reducers of power machines etc.) for calculating spur and helical gearing for deep contact strength. The author presents all necessary formulas and graphs for the implementation of each methods, and compares the calculations results of these methods with the results of experimental studies of cemented cylindrical rollers for deep contact destruction.